Communication breakdown in Italy's vaccination governance. (30th September 2020) - Attwell, K; Harper, T; Rizzi, M; Taylor, J; Casigliani, V; Quattrone, F; Lopalco, P L
Abstract: Background: In 2017, Italy rebooted its mandatory vaccination regime, following a series of unfavourable court decisions placing vaccination in disrepute. Vaccination rates had steadily declined for half a decade, culminating in a measles epidemic. Existing studies demonstrate the role of vaccine hesitancy, but none have explored the role of government in the years prior to the new mandate. This study analyses the drivers of failures to address sliding vaccine confidence in Italy. Methods: We engaged in qualitative analysis of primary sources, Italian and international scholarship, and semi-structured interviews with key informants. These were analysed using the coding software NVivo 12. We developed an empirically and theoretically informed schema to make sense of governance failures in knowledge and action. Results: The resort to mandates in 2017 was triggered by a series of unfortunate events, further thwarted by governance capacity gaps. During 2012-2017, Italy's vaccination governance included no online campaigns to address concerns. Public health officials lacked crucial knowledge regarding the population, including strategies to address hesitancy. They were preoccupied with other significant changes to Italy's vaccination governance, notably the vaccination schedule. Limited financial resources from the political class constrained officials' capacity in a context of austerity. A credibility gap ensued, which officials sought to plug by constructing Italians as in need of firm instruction by mandatory vaccination. Conclusions: When voluntary vaccination failed in Italy, the new mandates improved coverage rates. However, the vaccine confidence work explored in this study should not be neglected. The future governance of vaccine confidence requires that effective communications to address vaccine confidence be implemented Italy and other jurisdictions facing vaccine hesitancy and refusal problems. Key messages: We analyse the Italian government's response to the crisis of vaccine confidence prior to the introduction of mandates, in order to provide lessons for other governments. We identify and explain the gaps in governance capacity that prevented the addressing of sliding coverage rates.